Forage Accumulation of Spring and Summer Cover Crops in Western Kansas - L. M. Simon; A. K. Obour; J. D. Holman; S. K. Johnson; K. L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2021)
Intensification of no-till dryland cropping systems in western Kansas with cover crops (CCs) may provide important ecosystem services while also supplying annual forage for livestock. Two experiments were initiated in 2015 and 2016 near Brownell, KS, to determine the forage production potential of spring and summer CCs in a winter wheat-grain sorghum-fallow crop rotation. Cover crops were mechanically harvested as hayed forage to a height of 6 inches or mob-grazed with yearling heifers (weighing approximately 1000 lb each) stocked at 3 head/acre/day. Forage accumulation was determined for the hayed treatment using a small plot forage harvester, and samples of the grazed treatment were hand-clipped before and after grazing every year from 2015 to 2020. Results showed forage accumulation of spring CCs grown in place of fallow following grain sorghum averaged 2231 lb/a dry forage mass and ranged from 1427 to 2871 lb/a. Similarly, forage accumulation of summer CCs planted after wheat harvest averaged 2513 lb/a dry forage mass and ranged from 956 to 3718 lb/a. In 2017, summer CCs failed to produce a harvestable yield. Results suggest that CCs may provide desirable annual forage for livestock. However, forage accumulation of both spring and summer CCs was variable in this study. In years that spring CCs were planted early (before March 15), yields tended to be higher (>2200 lb/a) due to less susceptibility to heat and moisture stress. Summer CCs performed best when planted immediately following wheat harvest to take advantage of summer rains and to produce as much forage mass (>3000 lb/a in favorable years) as possible before the first killing frost or about October 15 for most of western Kansas.
Keywords: cover crops; dryland; forage; grazing